Storage Effect of Malaysian Cassava (Manihot Esculenta) Root Tubers on the Quality of Chips - Shamsudin, Rosnah; Chung, Ai Sing; Mohd Adzahan, Noranizan (2010)
Effect of storage time for tubers of cassava (Manihot esculenta) roots on crispiness of cassava chips was determined. After harvesting, cassava roots were stored up to 5 days in ambient temperature (27°C, 70-80% RH). The tubers were sliced to a thickness of 1 mm and cut into an oval shape (48 mm minor diameter x 50 mm major diameter). These slices were fried individually at 172ºC for 45s using 2L of vegetable oil (local palm oil). The hardness of chips decreased with increasing storage time. The decrease of hardness of cassava chips means the decrease in crispiness of fried cassava chips. The changes of colour of cassava chips during fried at three different temperatures (142ºC, 172ºC and 192º) was determined. Lightness in color of the chips decreased from 25.6 to 23.4, a* value increased from 2.0 to 2.6 and while the b* value increased from 14.4 to 17.9 with increasing frying temperature (142 to 192oC). This indicates that there was a gradual loss of quality in fried cassava chips when the tubers were stored after harvesting.